Perancangan Aplikasi Pendaftaran Magang Kantor Wilayah Kementerian Agama Provinsi Sumatera Selatan Berbasis Website - Kelpin Wahyu Pratama (Lembaga Pengembangan Kinerja Dosen, 2026)
Field Work Lectures (KKP) or Practical Work Lectures (PKL) are compulsory activities for students of Bina Darma University Palembang when entering the sixth semester. This program enables students to directly experience the working environment of agencies or companies while applying the knowledge acquired during lectures. KKP/PKL is also an essential academic requirement for continuing to the thesis proposal stage and is recognized as a practical work report course. In this program, the student carried out Practical Work Lectures at a government institution, namely the Regional Office of the Ministry of Religion of South Sumatra Province, located in Palembang. The activity was conducted for a duration of one month. The main objective of this Practical Work Lecture was to study existing procedures and design a modern internship registration system based on website technology. Through this activity, students are able to integrate theoretical knowledge with practical experience, gain a deeper understanding of real working conditions, and enhance professional skills. The implementation of KKP also provides valuable insights into organizational workflows and administrative systems. The outcomes of this activity are documented in a report focusing on the design of a website-based internship registration system intended to support administrative processes at the Regional Office of the Ministry of Religion of South Sumatra Province.